Strategies for the implementation of clinical services in a university pharmacy in the Brazilian Northeast: a situational strategic planning-based approach - Silva, Amanda Batista da; Dantas, Maria Jaíne Lima; Lucena, Othon Luís Souza de; Andrade Júnior, Francisco Patricio de; Rabelo, Elaine Cristina da Silva Ferreira; Souza, Júlia Beatriz Pereira de; Montenegro, Camila de Albuquerque (REVISTA CEREUS, 2025)
The study aimed to implement pharmaceutical clinical services at the Farmácia Escola Manoel Casado de Almeida, linked to the Federal University of Campina Grande (UFCG), Cuité-PB campus. The epidemiological profile of the population attending the Basic Health Units (UBS) in Cuité/PB was evaluated, and a socioeconomic, demographic, and medication use questionnaire was applied to the university community. A situational strategic planning was developed to guide the implementation of strategies for the inclusion of Clinical Pharmacy services to assist the population, and Pearson's Chi-Square test was used, with p<0.05 considered significant. There was a predominance of females in both analyses; at the UBS, individuals aged 60 or older (67%), farmers (23.5%), and hypertensive patients (73.7%) were more prevalent. On campus, the majority were individuals aged 20 to 29 (67.2%), with an income of up to half a minimum wage (24.5%), residents of the urban area (85.5%), and with incomplete/completed higher education (83.5%). Based on the profile found, the following services were offered: health education and screening, pharmacotherapy review, pharmaceutical follow-up, and medication organization procedures, blood pressure measurement, blood glucose testing, and anthropometric measurement determination. Conclusions: It was concluded that it was possible to structure the pharmaceutical clinical services to be provided at the Farmácia Escola.